LAND SLIDE ANALYSIS USING DIGITAL ELEVATION MODELS - Mawardi Mawardi; Makmun R. Razali; Cyntia Cyntia (Universitas Bengkulu, 2019)
Landslides almost every year occur in Indonesia, this rare landslide that can be detected early. because so far the prediction of slope slope is difficult. To predict the calculation requires the analysis and stability of the slope manually. This manual calculation process is quite long and long process. The calculation data and slope stability analysis are in the form of slope measurement, the work is quite tiring and risky for the researcher, and also the scope of the slope that can be measured is only narrow. In addition to slope inclination data, for slope analysis also requires soil data to be sampled and testing in a geotechnical laboratory. This study investigated slope stability by creating landslide models using Digital Elevation Models (DEM), and Geoslope programs. Slope model was analyzed from DEM and landslide stability analysis using Geoslope. From this concept we are expected to analyze landslide / stability slope quickly and accurately without risk for researcher. The results of lab tests were obtained:water content (wN), wN1 = 39.47%, wN1 = 40.54%, wN1 = 38.89%. Specific Soil Weight (Gs) ranged from 2.60 to 2.62, wet soil volume weight ranged from 14.59 to 16.16 kN / m3, the weight of saturated soil volume ranged from 15.59 to 16.82 kN / m3, the weight of soil volume dried ranged from 09.99 to 16.82 kN / m3, soil liquid limit ranged 61.26-66.06%, plastic limit of land ranged from 39.58 to 44.88%, soil plastic index ranged from 21.18 to 21.66, so that the soil is categorized as organic clay soil, the face of the soil at a depth of -0.5m, the cohesion value (c) ranges from 29.10 to 34.90 kPa, and the frictional angle values in the range 19.51 21.100, the slope of the slope ranges from 24 to 420 and slope safety figures (FK), on slopes 1 FK = 1.87 (slope safe against landslide hazard), on slope 2 FK = 1.20 (slope unsafe against landslide hazard), on slope 3 FK = 1.52 (the slope is safe from landslide hazards).